A Study on the Influence of Hot Press Forming Process Parameters on Flexural Property of Glass/PP Based Thermoplastic Composites Using Box-Behnken Experimental Design. (4th March 2014) - Kumar, B. Senthil; Balachandar, Subramanian
Abstract : A thermoplastic composite is produced from polypropylene matrix with glass fibre reinforcement. These types of composite materials are ecofriendly nature due to their reusability after their lifetime. These polymer composites are alternative to heavy metals that are currently being used in many non-structural applications. In spite of being ecofriendly nature, the range of applications is limited due to poor mechanical properties as compared with thermoset matrix composite. Hence an attempt was made in this work to improve the mechanical property such as flexural property of Glass/PP hybrid woven composites by optimizing the parameters during compression moulding, such as mould pressure, mould temperature, and holding time using Box-Behnken experimental design. Each process variables were taken in 3 different levels. Second order polynomial model with quadratic effect was chosen. The optimum combination of process parameters was obtained by using contour diagram. The levels of importance of process parameters on flexural properties were determined by using analysis of variance (ANOVA). The variation of flexural property with cited process parameters was mathematically modelled using the regression analysis.